Recovery of Lithium Carbonate from Nigerian Lepidolite Ore via Roasting-Leaching-Precipitation - Mohammed U. GARBA; Musa A. ABDULLAHI; Isah RABI; Saadatu A. GORO; Habibu UTHMAN; Abubakar S. MOHAMMED; Umaru AHMADU; Usman S. ONODUKU (FUDMA Journal of Engineering and Technology, 2025)
This study investigated the feasibility of extracting lithium from lepidolite ore sourced from Eggon, Nasarawa State, Nigeria, using a sulfuric acid roasting-water leaching method. The raw ore, a complex aluminosilicate with a low lithium content of 1.12%, underwent a multi-stage process involving calcination, acid roasting, water leaching, and precipitation. Characterization by X-ray diffraction (XRD), X-ray fluorescence (XRF), and scanning electron microscopy with energy-dispersive X-ray spectroscopy (SEM-EDX) confirmed successful mineralogical and chemical transformations at each stage. Calcination at 900 °C and subsequent roasting with sulfuric acid at 300 °C effectively activated the ore, converting lithium into a soluble sulfate. Subsequent leaching and purification steps led to the precipitation of lithium carbonate. The final product was a crystalline, lithium-rich powder, although some trace metals persisted. The results confirm the technical viability of this process for producing lithium carbonate, highlighting its potential for industrial application in battery manufacturing.
Keywords: Lepidolite, roasting, leaching, impurities, characterization, lithium carbonate.